A constitutional perspective on the connection between the state and the economy. Implications of the fundamental right in a decent standard of living - Niță, Anca Jeanina (Technium Social Sciences Journal, 2023)
Starting from an indisputable reality, namely that the numerous global and interconnected crises (pandemic crisis, biodiversity crisis, economic crisis and energy crisis, etc.) exacerbate the cost of living crisis and affect the right to a decent standard of living in all states of the world, the present study proposes a "radiography" of the decent standard of living in Romania - between the constitutional consecration and the social reality. The coordinates of the state-economy connection and of the standard of living in the consecration of the Romanian Constitution are presented. It starts from the proclamation of Romania - by the very article 1 of the Constitution, as a "governed by law, democratic and social state" and the provisions of art. 47-"Standard of living" and of art. 135 "Economy" are briefly analysed. Statistical data and conclusions from the "Social report: Quality of life during the pandemic: problems and response policies. A synthetic point of view" are highlighted. The cost of living crisis in Romania is observed from the point of view of the data provided by the study on the quality of life and social well-being - 2022, carried out by Social Progress Imperative with the support of Deloitte and by the conclusions expressed by the People’s Advocate in the "Special report on respect of the right to work and the social protection of work", published on January 26th, 2022. It is stated that the Romanian state continues to be, in the social sphere and from the point of view of turning the fundamental right to a decent standard of living into reality, the "poor relative" of the developed states of the European Union, that the policy of the "small" state is largely responsible for the vulnerability of our society in the current crisis and - as a possible solution aimed at contributing to the effectiveness of the right to a decent standard of living, the opinion according to which: "The quality of life in a governed by law, democratic and social state, a quality of life which is generated by fundamental social rights, should be declared, by law, a component of national security and of the safety of the person, as a human being" is appropriated.